Murchison widefield array observations of anomalous variability: A serendipitous night-time detection of interplanetary scintillation - Kaplan, D.; Tingay, Steven; Manoharan, P.; Macquart, Jean-Pierre; Hancock, Paul; Morgan, John; Mitchell, D.; Ekers, R.; Wayth, Randall; Trott, Cathryn; Murphy, T.; Oberoi, D.; et al. (Institute of Physics Publishing, 2015)
We present observations of high-amplitude rapid (2 s) variability toward two bright, compact extragalactic radio sources out of several hundred of the brightest radio sources in one of the Murchison Widefield Array (MWA) Epoch of Reionization fields using the MWA at 155 MHz. After rejecting intrinsic, instrumental, and ionospheric origins we consider the most likely explanation for this variability to be interplanetary scintillation (IPS), likely the result of a large coronal mass ejection propagating from the Sun. This is confirmed by roughly contemporaneous observations with the Ooty Radio Telescope. We see evidence for structure on spatial scales ranging from <1000 to > 10 6 km. The serendipitous night-time nature of these detections illustrates the new regime that the MWA has opened for IPS studies with sensitive night-time, wide-field, low-frequency observations. This regime complements traditional dedicated strategies for observing IPS and can be utilized in real-time to facilitate dedicated follow-up observations. At the same time, it allows large-scale surveys for compact (arcsec) structures in low-frequency radio sources despite the resolution of the array.